Postoperative Pain Management and Opioid Reduction in Oncologic Breast Surgery - Ahmad Ali, Nawaz Ali Dal, Ghulam Murtaza, Khushal Khan, Shua Nasir, Lal Shehbaz, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The opioid crisis in the United States has led to a national public health disaster. Opioid overdose deaths have grown dramatically, owing primarily to opioid overprescription for pain management. This research work looks into the usage of liposomal bupivacaine (LB) as a substitute to opioids. The primary application is for postoperative pain management in breast cancer surgery. Aims and Objective: The goal of this study was to see how well liposomal bupivacaine reduced postoperative pain. To assess opioid intake in patients experiencing a mastectomy, incomplete mastectomy, excisional biopsy and sentinel lymph node biopsy. Methods: This Retroactive research involved 60 female patients and was conducted at Liaquat institute of medical and health sciences jamshoro. These patients received breast cancer surgery between May 2022 and April 2023. Liposomal bupivacaine was delivered to patients through surgery. By using the Numerical Pain Rating Scale (NPRS they were followed up with pain assessments. Postoperative opioid and nonopioid analgesic usage were monitored. Results: Patients receiving liposomal bupivacaine reported significantly lower pain scores compared to those who did not, with NPRS scores reduced by postoperative day 7 (median: 1.2 vs. 2.2 for partial mastectomy; p<0.05). LB-treated patients required fewer opioids (median: 2.2 pills for excisional biopsies vs. 6.0 without LB; p<0.05). Non-opioid or no analgesics were sufficient for 38.2% of LB recipients, compared to only 7.7% in the non-LB group. The greatest opioid reduction was observed in less invasive procedures. Conclusion: Liposomal bupivacaine successfully alleviates postoperative pain and opioid use. This effect was predominantly evident in less invasive breast cancer operations. This treatment may support lessen the opioid problem via providing a practical analgesic option. Keywords: Postoperative recovery, liposomal bupivacaine, opioid reduction, pain management, breast surgery.